Improved ancilla preparation in spectral shearing interferometry for accurate ultrafast pulse characterization. - Witting, T; Austin, DR; Walmsley, I (2009)
We report a version of spectral phase interferometry for direct electric field reconstruction (SPIDER), in which spectral filters are used to produce the quasi-monochromatic fields required for upconversion. The advantages of this approach include improved calibration accuracy, robustness for strongly chirped input pulses, simplicity, and compactness. We verify the technique experimentally by measuring the spectral chirp of a grating compressor using a spatially encoded arrangement (SEA-)SPIDER.